2023
DOI: 10.3390/bdcc7040169
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Security KPIs for 5G Network Slices for Special Groups of Subscribers

Roman Odarchenko,
Maksim Iavich,
Giorgi Iashvili
et al.

Abstract: It is clear that 5G networks have already become integral to our present. However, a significant issue lies in the fact that current 5G communication systems are incapable of fully ensuring the required quality of service and the security of transmitted data, especially in government networks that operate in the context of the Internet of Things, hostilities, hybrid warfare, and cyberwarfare. The use of 5G extends to critical infrastructure operators and special users such as law enforcement, governments, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…3GPP recommends network slice performance and fault monitoring in multi-tenant environments [52]. Odarchenko et al [53] proposed a security assessment index and method that can be used in 5G network slicing systems. This method can conduct security monitoring for special user groups and achieve the reliable operation of multi-tenant slicing services.…”
Section: Multi-tenant Scenario Security Requirements and Recommendationsmentioning
confidence: 99%
“…3GPP recommends network slice performance and fault monitoring in multi-tenant environments [52]. Odarchenko et al [53] proposed a security assessment index and method that can be used in 5G network slicing systems. This method can conduct security monitoring for special user groups and achieve the reliable operation of multi-tenant slicing services.…”
Section: Multi-tenant Scenario Security Requirements and Recommendationsmentioning
confidence: 99%
“…Makarchuk & I. Fedulova (2023), issues of cyber security of computer devices, methods of protection against unauthorised disclosure of confidential information of consumers are considered. In the article of the authors R. Odarchenko et al (2023) the connection between the development of communication networks and the implementation of internationally accepted 5G standards is shown. It is shown that the transition to the 5G network requires compliance with cyber hygiene to prevent cyber threats.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of heterogeneous wireless networks aims to overcome the limitations of a single technology and protocol by effectively integrating multiple technologies, providing a more flexible and efficient communication solution. While widely applied, heterogeneous wireless networks also face multiple challenges, such as spectrum resource management, mobility management, and security management [1][2][3].…”
Section: Introductionmentioning
confidence: 99%